The protection of traditional knowledge on genetic resources - Papadopoulou, Frantzeska (Edward Elgar Publishing, 2018)
Traditional knowledge protection methods are becoming increasingly out-dated in the face of modern challenges. Focusing on the protection of traditional knowledge and related genetic resources, this book is the first of its kind to amalgamate a novel theoretical framework with the practical applications of the combined theories of Rawls and Coase. The Protection of Traditional Knowledge on Genetic Resources analyses various means of protection for traditional knowledge that cohere with Rawls' and Coase's specific objectives regarding fairness and efficiency. It utilizes flexibilities provided by binding international conventions in the field in order to propose alternative methods to protect different forms of traditional knowledge-based innovation. Frantzeska Papadopoulou reaches the conclusion that property, liability and reward systems are forms of protection that fulfil the fairness and efficiency criteria whilst remaining compliant with the general international legal framework. This book is ideal for intellectual property law and development academics and policymakers, especially those working on intellectual property rights (IPRs), as it proposes a novel methodological framework for the evaluation of new as well as existing IPRs.